Rational/Statistical Method of Test Validation - Pinder, Craig (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This study demonstrates the application of a test validation procedure similar to that described by Mobley and Ramsay (1973) but which avoids the use of factor analysis in isolating dimensions upon which subsequent job subgrouping is based. Instead, a semi-judgmental, semi-statistical method was employed. Actual test validation data are reported which, although missing in Mobley and Ramsay's (1973) article, attest to the utility of a job grouping approach to the validation problem.